2018
DOI: 10.1007/s00520-018-4064-x
|View full text |Cite
|
Sign up to set email alerts
|

The TEACHH model to predict life expectancy in patients presenting for palliative spine radiotherapy: external validation and comparison with alternate models

Abstract: The TEACHH model is useful to identify patients with spinal metastases with predicted short, intermediate, and long LE. Its prognostic ability is similar to the Chow model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…-10 months reported by Chow et al for the three risk groups based on their training, temporal validation and external validation dataset. In comparison, the median OS of our patients with 0-1, 2-4 and 5-6 TEACHH risk factors were 15.4, 3.5 and 0.6 months respectively; these were similar to the corresponding 19.9, 5 and 1.7 months reported by Krishan et al Similar results of the NRF and TEACHH models were reported by Dosani et al based on a cohort of Canadian patients treated with palliative RT for spinal metastases(14). Of the three NRF factors, only site of disease and metastases were significantly associated with OS.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…-10 months reported by Chow et al for the three risk groups based on their training, temporal validation and external validation dataset. In comparison, the median OS of our patients with 0-1, 2-4 and 5-6 TEACHH risk factors were 15.4, 3.5 and 0.6 months respectively; these were similar to the corresponding 19.9, 5 and 1.7 months reported by Krishan et al Similar results of the NRF and TEACHH models were reported by Dosani et al based on a cohort of Canadian patients treated with palliative RT for spinal metastases(14). Of the three NRF factors, only site of disease and metastases were significantly associated with OS.…”
supporting
confidence: 91%
“…The TEACHH model developed by Krishnan et al stratified patients into three prognostic groups based on cancer type, Eastern Cooperative Oncology Group (ECOG) performance status, age, prior palliative chemotherapy, prior hospitalisation and hepatic metastases (11). Both models have been externally validated in several studies, and have shown to be effective tools in the Caucasian population (10,(12)(13)(14). Currently, data on the performance of these models in Asian populations is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Newer therapies such as immunotherapy are emerging, which may alter cancer progression and mortality. While all three prognostic models were developed prior to wide spread use of immunotherapy, it is helpful to note that the Chow NRF model, which was developed among patients seen in 1999, still performs quite well among more contemporary cohorts (19,21,22), who inevitably are being exposed to newer systemic agents.…”
Section: Estimating Life Expectancy For Patients and Treatment Recomm...mentioning
confidence: 99%
“… [3] , [4] , [5] As such, a number of prognostic models have been developed in order to support improved prognostication and thus better informed treatment decisions. [6] , [7] , [8] , [9] Multiple models have been developed in palliative radiotherapy where the decision to treat and to fractionate may vary with the expected prognosis of the patient.…”
Section: Introductionmentioning
confidence: 99%